2018
DOI: 10.1039/c7ta11320j
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of highly permeable thin-film nanocomposite forward osmosis membranes via the design of novel freestanding robust nanofiber substrates

Abstract: Although forward osmosis (FO) technology is considered to be a sustainable solution for the water and energy shortage, it has not been commercialized yet due to a few factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 60 publications
2
17
1
Order By: Relevance
“…Notably, the diffraction peaks of PVDF nanofibers were in agreement with those of the powder except the disappearance of the weak peaks at 2θ of 17.9°, 26.7°, and 38.8°, indicating that the nanofibers were still dominated by the α-phase, which was inconsistent with the previous view that electrospinning PVDF often produces piezoelectric nanofibers with the β-phase via in situ electric field poling and mechanical stretching . The reason might be due to the higher average molecular weight of PVDF ( M w = 573 000 g/mol) used in this study compared with that of the reported literatures ( M w = 275 000 g/mol). , Conversely, with respect to PVDF nanofiber/nanonets, all of the above diffraction peaks totally vanished and two new peaks at 2θ of 20.7° and 36.5° appeared, which were attributed to the polar TTTT conformation of β-crystalline phase and corresponded to (110/200) and (020) reflection planes . Therefore, the α → β phase transition in electrospun/netted PVDF nanofiber/nanonets was achieved, and such transition could be further confirmed by the recorded FT-IR spectra.…”
Section: Resultscontrasting
confidence: 55%
“…Notably, the diffraction peaks of PVDF nanofibers were in agreement with those of the powder except the disappearance of the weak peaks at 2θ of 17.9°, 26.7°, and 38.8°, indicating that the nanofibers were still dominated by the α-phase, which was inconsistent with the previous view that electrospinning PVDF often produces piezoelectric nanofibers with the β-phase via in situ electric field poling and mechanical stretching . The reason might be due to the higher average molecular weight of PVDF ( M w = 573 000 g/mol) used in this study compared with that of the reported literatures ( M w = 275 000 g/mol). , Conversely, with respect to PVDF nanofiber/nanonets, all of the above diffraction peaks totally vanished and two new peaks at 2θ of 20.7° and 36.5° appeared, which were attributed to the polar TTTT conformation of β-crystalline phase and corresponded to (110/200) and (020) reflection planes . Therefore, the α → β phase transition in electrospun/netted PVDF nanofiber/nanonets was achieved, and such transition could be further confirmed by the recorded FT-IR spectra.…”
Section: Resultscontrasting
confidence: 55%
“…On the contrast, the micro-length of the NFs (micro-sized) would hinder their release during the filtration and/or phase-inversion process, compared to the NPs [26]. Fortunately, NFs can be fabricated easily using the electrospinning technique [27][28][29][30][31], electrospinning can produce continuous nanofibers with nano-sized to submicron diameters and micro-sized length, moreover, sub-nanometer fibers were produced recently [32]. It is important to mention that, unlike the NPs, the orientation of NFs is critical where its micro-sized length can lengthen the water transport path and decrease the pore size if the fibers are oriented horizontally inside the membrane matrix (perpendicular to the crosssection).…”
Section: Introductionmentioning
confidence: 99%
“…The new and strong peaks at 3460 and 1625 cm –1 ascribed the N–H stretching vibration of piperazine, and the CO stretching vibration of the amide group, respectively. , The adsorption peaks at 1438 and 1363 cm –1 corresponded to the C–N stretching vibration of −CO–NH– groups . On the contrary, the intensities of 1723, 1486, and 1151 cm –1 peaks attributed to ester groups (−COO−) of carboxyl groups from a linear structure (Scheme ), benzene ring and C–C bond stretching, and symmetrical stretching vibrations of the −SO 2 – groups from PSf support membrane were greatly suppressed. Overall, the above results indicate that the PPA layer was formed enough to cover the surface of PSf support layer when increasing its electrospray time.…”
Section: Resultsmentioning
confidence: 99%